Reduction of Real Power Loss and Safeguarding of Voltage Constancy by Artificial Immune System Algorithm - Kanagasabai Lenin; B.Ravindhranath Reddy; M. Suryakalavathi (Bulletin of Electrical Engineering and Informatics, 2015)
In this paper, Artificial Immune System (AIS) algorithm is used for solving reactive power problem.  Artificial Immune System Algorithm, also termed as the machine learning approach to Artificial Intelligence, are powerful stochastic optimization techniques with potential features of random search, hill climbing, statistical sampling and competition. Artificial immune system algorithmic approach to power system optimization these ideas are embedded into proposed algorithm for solving reactive dispatch problem. In order to evaluate the proposed algorithm, it has been tested in standard IEEE 30,118 bus systems and compared to other specified algorithms. Simulation results show better performance of the proposed AIS algorithm in reducing the real power loss and preservation of voltage stability.